Finite element simulation on residual stress during immersion quenching and pre-stretching of Al7055 thick plates - Kai Zhu; Baiqing Xiong; Xiwu Li; Yongan Zhang; Zhihui Li; Yanan Li; Kai Wen; Lizhen Yan (Materials Research Express, 2022)
During the immersion quenching process, severe temperature changes and significant temperature differences between the core and superficial area can give rise to high residual stresses within the aluminum alloy thick plate to cause subsequent machining distortion of the thin-walled part. Reducing the residual stress within the thick plate can effectively minimize the distortion in part. In this research, ABAQUS software was adopted to simulate the internal temperature and stress fields of thick plates of Al7055 alloy during the quenching and pre-stretching processes, sequentially and respectively. In addition, the x-ray residual stress measurement method was used to measure and characterize the surface residual stress of the plates. The results indicate that the medium temperature affects residual stress inside the thick plate significantly during the immersion quenching process. The level of which inside the plate gradually increases as the medium temperature decreases. Further, the pre-stretching treatment can effectively reduce residual stresses within the thick plate, and the residual stress level gradually decreases with the pre-stretching ratio increasing. The experimental results verify the feasibility of numerical simulation to predict the status of quenching stress in thick plates. Subsequently, a simulation study for material removal processes was carried out based on the above studies. The results reveal that the thin-walled part’s machining distortion degree improves as the raw thick plate’s initial quench residual stress level decreases.